Acid rain intrusion effects on the compressibility behaviour of residual soils. Issue 7 (21st December 2017) - Bakhshipour, Zeinab; Asadi, Afshin; Sridharan, Asuri; Huat, Bujang B K
Abstract : This paper presents the results of experiments designed to investigate the effect of acid rain on the compressibility behaviour of residual soils. Sedimentary residual soil (SRS) and igneous residual soil (IRS) with different mineral compositions were collected from two locations in Malaysia. The specimens were infiltrated by artificial acid rain (AAR) at varying pH values of 2, 3, 4, 5 and 5·6 and at different fluxes of 1, 5 and 20 years. At the end of each AAR flux interval, compressibility, zeta potential, atomic adsorption spectroscopy, X-ray diffraction and scanning electron microscope analyses were performed to study the behaviour of the soil in an acidic environment. It was found that AAR has a strong effect on soil structure; consequently, the compressibility of both SRS and IRS increased as the pH value decreased and/or as the flux of AAR increased. Microstructural analyses confirmed that this process destroyed the bonds between clay particles/aggregates and induced significant changes in mineral structure due to the dissolution of alumina and silica from SRS and IRS, resulting in the formation of 'loose' structures with larger voids.